1998
DOI: 10.1097/00005082-199807000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Patient Education for Discharge after Coronary Bypass Surgery in the 1990s: Are Patients Adequately Prepared?

Abstract: Short hospitalizations for patients undergoing coronary artery bypass grafting (CABG) require continuous nursing evaluation of patients' discharge education. Six institutions collaborated in surveying 300 postoperative patients with CABG to identify learning priorities and patients' perceptions of the effectiveness of discharge education. Data analysis from the self-administered questionnaire demonstrated consistent patient priorities across institutions. Differences in teaching methods and content did not aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 0 publications
4
23
0
2
Order By: Relevance
“…Alkubati et al, (2012) study found similar results, in which the most frequent learning needs were the chest and leg wound care, while the least frequent was physical activity. Also, it was consistent with Beggs et al(1998) who found that complications, chest and leg incision care and whom to call, were the most ranked learning needs while the least one was the physical activity. In addition, it was consistent with the Al-Qissi study (2003) who found that wound care, followed by complications and symptoms information, ending with risk factors most reported learning needs among Jordanian CABG patients.…”
Section: Most Frequent Learning Needs Among Cabg Patientssupporting
confidence: 82%
“…Alkubati et al, (2012) study found similar results, in which the most frequent learning needs were the chest and leg wound care, while the least frequent was physical activity. Also, it was consistent with Beggs et al(1998) who found that complications, chest and leg incision care and whom to call, were the most ranked learning needs while the least one was the physical activity. In addition, it was consistent with the Al-Qissi study (2003) who found that wound care, followed by complications and symptoms information, ending with risk factors most reported learning needs among Jordanian CABG patients.…”
Section: Most Frequent Learning Needs Among Cabg Patientssupporting
confidence: 82%
“…Patients continue to deal with these issues at home after discharge without health professional support (Beggs et al, 1998;Moore, 1994Moore, ,1995Tack and Gillis, 1990;Wu, 1995), even up to 12 weeks postdischarge (Lenz and Perkins, 2000). Several patients expressed concem about thefu pain management after discharge and hoped that "my doctor will give me pain killers when I go home".…”
Section: Discussionmentioning
confidence: 99%
“…Several patients expressed concem about thefu pain management after discharge and hoped that "my doctor will give me pain killers when I go home". In several studies, patients identified the need for information about pain management to help with the recovery period after discharge (Beggs et al, 1998;Goodman, 1997). Weber et al (1996) found that pain was one reason King (2000) found that women continued to report soreness in chest and leg incisions at 3 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Os pacientes do presente estudo atribuíam à dor na região torácica suas dificuldades para desenvolverem movimentos respiratórios amplos, tossir ou mesmo encontrar posições confortáveis para induzir e manter o sono. Assim, as preocupações e os problemas relacionados à ferida cirúrgica são aspectos importantes a serem abordados pelos enfermeiros junto aos pacientes além de ser um dos temas prioritários para a educação dos pacientes (31) .…”
Section: Discussionunclassified
“…A educação do paciente é um importante aspecto na assistência de enfermagem. O preparo do revascularizado para o auto-cuidado requer informações específicas sobre os problemas observados neste estudo e por outros autores (3,11,(27)(28)31,35) . (36) .…”
Section: Discussionunclassified